Innovation and Networking as a Succession Strategy for the JNC Cookies Family Bussines: Inovasi Dan Networking sebagai Strategi Suksesi Family Bussines JNC Cookies - Galih Putra Wardana; Aldy Yonanda; Feby Restu Rachmariandre; Aris Tri Saputra; Rifdah Abadiyah (Procedia of Social Sciences and Humanities, 2026)
This study aims to analyze the family business succession strategy at JNC Cookies through the application of innovation and networking to ensure business sustainability. Family businesses play a vital role in the economy but often face challenges during the intergenerational leadership transition process. This study employs a descriptive qualitative method, using data collection techniques such as observation and in-depth interviews with the business owner, the next generation, and the management of JNC Cookies. The results indicate that product and marketing innovation are key factors in enhancing the company’s competitiveness. JNC Cookies drives innovation through the development of new flavor variants, attractive and eco-friendly packaging designs, and the use of digital media as a promotional tool. Furthermore, the network built with suppliers, resellers, distributors, and other business partners has proven effective in expanding the market and maintaining business stability. A succession strategy that actively involves the next generation also helps the company sustain the family business amid increasingly competitive conditions in the food industry. Thus, the combination of succession strategy, innovation, and networking is a critical factor in ensuring the long-term sustainability of JNC Cookies. Highlights: Developing novel flavor profiles and sustainable packaging guarantees market competitiveness. Establishing robust reseller ecosystems mitigates operational risks during leadership transitions. Active next-generation involvement synchronizes traditional values with modern digital promotions. Keywords: Leadership Transitions, Eco-Friendly Packaging,Distribution Ecosystems, Product Differentiation, Collaborative Partnerships